Immediate Effects of Kinesiotape on Gait and Static Weight-Bearing in Dog - Altinkaya, N; Pekyavas, NO; Gungor, GC (Journal of the Hellenic Veterinary Medical Society, 2025)
While the advantages of Kinesiotape applications in animals are acknowledged, there remains a gap in controlled studies specifically focusing on dogs. This study aims to assess the impact of Kinesiotape application in dogs experiencing gait issues. Twenty dogs presenting with gait abnormalities were randomly allocated into two groups. The experimental group (KT,n=10) received Kinesiotape application, while the control group (CG,n=10) received identical taping with rigid tape. Gait duration, step count, and static weight-bearing scores were measured both before and after tape application. The KT group demonstrated a significant improvement in the number of steps taken, gait duration, and weight-bearing compared to baseline (p<0.05). In contrast, the CG exhibited improvement only in gait duration, with non-significant changes in the number of steps and weight-bearing (p>0.05). Between-group comparisons revealed that the KT group exhibited superior outcomes in both the number of steps and weight-bearing (p<0.05), while no significant difference was observed between the two groups regarding gait duration (p>0.05). Our findings suggest that Kinesiotape application yields superior outcomes compared to rigid taping concerning gait and static weight transfer in dogs. Importantly, this study represents the first randomized controlled trial examining Kinesiotape application in dogs.